Exercise‐Regulated Irisin Signaling in Glucose Homeostasis and Diabetes: The Myogenic Benefits for Metabolic Health - Ruolin Gao; Yong Zhang; Lei Quan (Comprehensive Physiology, 2026)
ABSTRACT The myokine revolution has dramatically shifted the paradigm of integrated physiology, bridging exercise adaptations to the prevention of a wide range of chronic diseases. Exercise stimulates irisin synthesis and secretion, which not only regulates musculoskeletal functions but also improves physical performance and metabolic homeostasis through its autocrine, paracrine and endocrine functions. This myogenic exerkine has now been recognized to be produced by multiple tissues and exert metabolic health benefits through pleiotropic effects, that is, promoting white adipose tissue browning, enhancing glycolipid metabolism, increasing energy expenditure and modulating insulin sensitivity. Evidence supports the emerging roles of irisin as a potential biomarker and treatment target for further investigation in Type 2 diabetes mellitus (T2DM), although the therapeutic effects may depend on tissue origin, metabolic status and other factors such as sex and body mass index. Moreover, methodological challenges remain in accurately measuring circulating irisin levels. Given the complex interplay among exercise, irisin and T2DM, this review aims to elucidate the molecular mechanisms by which irisin mediates organ crosstalk and ameliorates insulin resistance (IR) from a perspective of exercise biology. Our work provides a theoretical foundation for improving exercise‐based T2DM prevention and treatment strategies. Although the pleiotropic effects of irisin position it as an intriguing molecular candidate, we also emphasize that direct causal evidence in humans remains scarce, and that irisin should currently be viewed as an experimental molecule rather than a validated clinical target for T2DM, given the lack of randomized controlled trials and the unresolved causal questions.